Kikuchi-Fujimoto disease mimicking hematological malignancy: a case report - Yarkıcı, Hakan; Elyiğit, Faruk; Peker, Ahmet; Solakoğlu Kahraman, Dudu; Erbil, Nilgün; Akar, Harun (The European Research Journal, 2019)
Kikuchi-Fujimoto disease or histiocytic necrotizing lymphadenitis is a benign histopathological condition and a rare cause of lymphadenopathies. This disease which is seen in women around the age of 30 in the far east countries is generally presented with lymphadenopathy, fever, weight loss, and myalgia symptoms. In this article, we would like to present a case of Kikuchi-Fujimoto disease in the histopathology of the lymph node excision, which was examined in terms of lymphadenopathy.